Following Job's feet: A psychoanalytic perspective - Van der Zwan, Pieter (Stellenbosch theological journal, 2022)
The feet are the base of the body but suggest mobility at the same time. As such an important corporeal part to be expected is that figurative language would develop around it hinting at unconscious associations to feet which might not be consciously logical. In the Book of Job the protagonist’s feet are mostly referred to as metaphors and then mainly with negative connotations. This is both because of the Satan’s attack on a man whom he suspects of having moral feet of clay and because of Job’s internal feuds with the feminine. Job experiences this as a sense of falling. A psychoanalytic perspective on metaphors for behaviour and especially on sexual euphemisms could penetrate through the façade of possible political correctness to add to a deeper understanding than the traditional exegesis has rendered thus far and give a glimpse of an underlying body-image.